The role of SH3RF2 in lung squamous cell carcinoma and M2 polarization: insights into LZTS2 ubiquitination - Jie Yang; Zhongfei Jia; Juan Li; Chao Jiang; Xin Zhao; Yuxiang Wang; Xiaoguo Ma; Xinjian Xu (Biology Direct)
Abstract Background Despite significant advancements in therapeutic approaches for lung cancer, the prognosis of lung squamous cell carcinoma (LUSC) remains suboptimal, underscoring the critical need to identify novel molecular targets and develop targeted therapeutic strategies. Through bioinformatic analysis, SH3RF2 was identified as a gene significantly upregulated in LUSC patients, and its high expression was strongly associated with lower survival rates. However, no significant differences in expression or survival correlation were observed in lung adenocarcinoma. Notably, SH3RF2, an E3 ubiquitin ligase characterized by three SH3 domains, has not been systematically investigated in LUSC pathogenesis. Results Mechanistic investigations found that SH3RF2 promoted tumor cell proliferation, upregulated M2 markers (Arg-1, CD163, IL-10), increased CD206 + subpopulation of M0 THP-1 cells and enhanced migration and invasion of M0 THP-1 cells. SH3RF2 promoted the nuclear translocation of β-catenin. Furthermore, ICG-001, the inhibitors of β-catenin pathway, alleviated the above effects of SH3RF2. In vivo tumorigenesis experiments found that SH3RF2 promoted tumor growth and increased the proportion of M2 cells. Proteomic analysis revealed that SH3RF2 interacted with LZTS2 and regulated the ubiquitination of LZTS2 with RING domain. Overexpression of LZTS2 attenuated SH3RF2-induced nuclear translocation of β-catenin, suppressed cellular migration and invasion, and inhibited M2 polarization promoted by SH3RF2 overexpression. The combination of SH3RF2 knockdown and radiotherapy inhibited the growth of tumor compared with SH3RF2 knockdown or radiotherapy alone. Conclusions This study demonstrates the functionality of SH3RF2 in both potentiating tumor progression and inducing M2 macrophage polarization through coordinated regulation of LZTS2 degradation and β-catenin nuclear translocation. These findings establish a novel mechanistic framework and propose SH3RF2-associated signaling axes as promising therapeutic targets for LUSC.